Skema Proteksi Resonansi Tegangan Lebih Saluran Udara Tegangan Ekstra Tinggi 500 kV - Imam Ghozali; Mochammad Facta; Abdul Syakur (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Shunt reactors are frequently installed at the end of a 500 kV double circuit extra high voltage transmission lines (EHVTL) to help overcome the voltage rise caused by the long line capacitance. However, voltage problems may still occur, especially during the voltage injection process in new transmission lines that have been installed, due to voltage induction and parameter reinforcement from other circuits within the same line that have been injected earlier. The problem of overvoltage occurrence becomes even more complex because the line and shunt reactor have been completely installed, making it impossible to change the length of the line and the capacity of the shunt reactor. The overvoltage phenomenon in this research occurs when one circuit in the transmission line has not been injected. However, the shunt reactor has been connected so that the line receives induction and strengthening from another circuit because, at the same time, the second circuit has been injected with operating voltage. Overvoltage in this research occurs when one circuit in the transmission line has not been injected. Nevertheless, the shunt reactor has been connected so that the line receives induction and reinforcement from another circuit because, at the same time, the second circuit has been injected with operating voltage. This paper proposes modifications to the voltage injection maneuver scenario into the line, modifications to the protection scheme in the event of a phase-to-ground fault, and the addition of an overvoltage relay to overcome the overvoltage conditions. Modifying the voltage injection maneuver scenario could decrease the overvoltage on lines not injected with voltage up to 31.9 kVp. Changing the protection scheme when a phase-to-ground fault occurred by commanding the shunt reactor’s circuit breaker (CB) to open could prevent voltage rises in the undisturbed phase. A voltage relay was added in order to anticipate the occurrence of overvoltage when there was a disturbance in the line, and the shunt reactor CB could not open due to internal disturbances.